Mengukur Kinerja Perusahaan dengan Penerapan Metode Balanced Scorecard pada PT. Perkebunan Nusantara VIII Kebun Sukamaju Cibadak Kabupaten Sukabumi - Hikmah Nurfaidah; R.Deni Muhammad Daniel; Faizal Mulia Z (IPM2KPE, 2020)
The purpose of this research is to find out how effective and efficient the application of the Balanced Scorecard method to company performance at PTPN. The method used in this research is to use the Balanced Scorecard method. Type of quantitative descriptive research. Data collection techniques used by researchers in this research is through observation, interviews, documentation, and literature studies. The results of calculations using the customer retention formula with a percentage of the company's ability to retain old customers can be said to be less good. Conclusions, the application of the balanced scorecard method at PT. Perkebunan Nusantara VIII, Sukamaju plantation, is more comprehensive and measurable, so it is good and needs to implement company performance measurement using the balanced scorecard method. Because to make it easier for management to control and evaluate company performance so they can survive in business competition and design corporate strategies for the long term. Keywords: Balanced Scorecard, Company Performance